2018
DOI: 10.1051/0004-6361/201731696
|View full text |Cite
|
Sign up to set email alerts
|

The Penn State - Toruń Centre for Astronomy Planet Search stars

Abstract: Context. Our knowledge of the intrinsic parameters of exoplanets is as precise as our determinations of their stellar hosts parameters. In the case of radial velocity searches for planets, stellar masses appear to be crucial. But before estimating stellar masses properly, detailed spectroscopic analysis is essential. With this paper we conclude a general spectroscopic description of the Pennsylvania-Toruń Planet Search (PTPS) sample of stars. Aims. We aim at a detailed description of basic parameters of stars … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 84 publications
3
16
0
Order By: Relevance
“…The sample presented in this paper comprises a total of 15 Li-rich giants from PTPS with the highest Li content, A(Li) NLTE ≥ 1.4 (Adamów et al 2014). HD 181368 was added to this list because this star was identified as a giant by Deka-Szymankiewicz et al (2018), and it was found to be a Li-rich giant as well. Twelve objects are the subject of detailed analysis, as new epochs of precise RV were collected in a quest for possible companions around them within the TAPAS project.…”
Section: Sample and Observationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sample presented in this paper comprises a total of 15 Li-rich giants from PTPS with the highest Li content, A(Li) NLTE ≥ 1.4 (Adamów et al 2014). HD 181368 was added to this list because this star was identified as a giant by Deka-Szymankiewicz et al (2018), and it was found to be a Li-rich giant as well. Twelve objects are the subject of detailed analysis, as new epochs of precise RV were collected in a quest for possible companions around them within the TAPAS project.…”
Section: Sample and Observationsmentioning
confidence: 99%
“…A detailed description of the atmospheric parameters can be found in Zieliński et al (2012) and Niedzielski et al (2016a). Masses, radii, and stellar ages were adopted from Deka-Szymankiewicz et al (2018).…”
Section: Sample and Observationsmentioning
confidence: 99%
See 3 more Smart Citations